Efficacy of a Second-Grade Science Program: Increasing Science Outcomes for All Students. (June 2021) - Doabler, Christian T.; Therrien, William J.; Longhi, Maria A.; Roberts, Greg; Hess, Katherine E.; Maddox, Steven A.; Uy, Jasmine; Lovette, Gail E.; Fall, Anna-Maria; Kimmel, Georgia L.; Benson, Sarah; VanUitert, Victoria J.; et al.
This study, which was reviewed through the Registered Report process, examined the initial efficacy of the Scientific Explorers program (Sci2) on second-grade students' science achievement. Sci2 is grounded in the growing body of empirical research on science instruction, embedding principles of explicit instruction within a guided inquiry-based design framework. Eighteen second-grade classrooms were randomly assigned to treatment or control conditions. A cluster randomized controlled trial was employed, with 294 students nested within classrooms and classrooms nested within condition. The Sci2 program was implemented for a total of 10 lessons (5 hr) in treatment classrooms, whereas control classrooms provided business-as-usual science instruction. Overall treatment effects were observed on three of four science outcome measures. The reported effects were moderate to large, with effect sizes (Hedges' g ) ranging from 0.48 to 0.94. Moderation analyses indicated that science knowledge at pretest did not moderate Sci2's effects. Implications for practice and research are discussed.